2000
DOI: 10.1161/01.atv.20.4.1168
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Thrombus Formation by Hyaluronic Acid Coating of Endovascular Devices

Abstract: Abstract-Biocompatible stent coatings may alleviate problems of increased (sub)acute thrombosis after stent implantation. Hyaluronic acid (HA), a ubiquitous, nonsulfated glycosaminoglycan, inhibits platelet adhesion and aggregation and prolongs bleeding when administered systemically. However, the effects of immobilized HA for reducing stent platelet deposition in vivo are unknown. We therefore quantified the antithrombotic effects of coating stainless steel stents and tubes with HA using an established baboon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 26 publications
5
90
0
1
Order By: Relevance
“…These results are consistent with other research groups that have shown that polymer surfaces coated with HA are relatively passive toward platelet adhesion and activation, 18,19,59 while stainless steel promotes platelet adhesion and activation. 19 On the RGD-HA surface [ Fig. 4(d)] rounded and partially spread platelets were observed, but very few (if any) spread platelets were present.…”
Section: Ha Attachmentsupporting
confidence: 93%
See 3 more Smart Citations
“…These results are consistent with other research groups that have shown that polymer surfaces coated with HA are relatively passive toward platelet adhesion and activation, 18,19,59 while stainless steel promotes platelet adhesion and activation. 19 On the RGD-HA surface [ Fig. 4(d)] rounded and partially spread platelets were observed, but very few (if any) spread platelets were present.…”
Section: Ha Attachmentsupporting
confidence: 93%
“…As mentioned, the lack of platelet adhesion on the HA-coated surface is consistent with other reports, 18,19,59 and indicates that the HA is adequately coating the sample and is masking the underlying aldehyde, silane, and steel. Presumably, platelets sedimented onto the HA surface during the 30 min of incubation, but they may not have adhered sufficiently to resist removal during the mild rinsing procedure.…”
Section: Ha Attachmentsupporting
confidence: 90%
See 2 more Smart Citations
“…163 New catheter materials in the clinical and preclinical stage of development, such as Hyaluronic Acid coated catheters and AT-heparin covalent complex coated catheters may prove to be useful in the future. 204,205 The latter is of particular interest in newborns who have decreased levels of AT.…”
Section: 2138mentioning
confidence: 99%